ANALISIS CIVIC DIGITAL LITERACY PADA MAHASISWA PPKN UNIVERSITAS LAMPUNG DALAM MERESPON KONTEN SATIRE POLITIK DI INSTAGRAM - Dewantara, Muhammad Bagus; Adha, Muhammad Mona; Siswanto, Edi; Nurmalisa, Yunisca; Fernanda, Fitra Endi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has transformed political communication, particularly through the emergence of political satire content on Instagram as a medium of social criticism. This phenomenon requires students to possess civic digital literacy in order to understand and respond to political information critically and responsibly. This study aims to analyze the civic digital literacy of PPKn students at the University of Lampung in responding to political satire content on Instagram. This research employed a qualitative approach with a descriptive method. The informants consisted of eight PPKn students and one political satire content creator selected purposively. Data were collected through interviews, observation, and documentation, and analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The results indicate that students’ civic digital literacy is reflected in aspects of knowledge, values, and skills. Students are able to interpret satire as social criticism, apply critical thinking in evaluating political information, and verify content before responding. Furthermore, they demonstrate ethical awareness and digital responsibility in social media interactions. Thus, it can be concluded that PPKn students at the University of Lampung have good civic digital literacy in responding to political satire content on Instagram.